Features of optical coherence tomography for the diagnosis of Vogt-Koyanagi-Harada disease - Liu, Xi Yao; Jonas, Jost B. (Retina, 2016)
Background/Purpose: To examine the diagnostic value of optical coherence tomography (OCT) for the detection of acute Vogt-Koyanagi-Harada (VKH) disease. - Methods: Clinical charts and OCT images were retrospectively reviewed for patients consecutively diagnosed with acute VKH, subacute VKH, multifocal central serous chorioretinopathy (CSCR), and posterior scleritis. All patients underwent OCT, fundus photography, and fluorescein angiography (FA) before treatment. The characteristics of OCT and FA were analyzed and recorded. - Results: The study included 80 eyes with acute VKH, 32 eyes with subacute VKH, 33 eyes with CSCR, and 13 eyes with posterior scleritis. The most common OCT features of VKH disease were hyperreflective dots (70/80; 88%), subretinal membranous structures (64/80; 80%), retinal detachment higher than 450 μm (63/80; 79%), and retinal pigment epithelium (RPE) folds (44/80; 55%). For the detection of VKH disease, sensitivity and specificity were for subretinal membranous structures 80% and 95.6%, respectively, for high retinal detachment 78.8% and 76.1%, respectively, for subretinal hyperreflective dots, 87.5 and 60.9%, respectively, and for RPE folds 55% and 80.4% respectively. Subretinal membranous structures showed the highest positive predictive value (97.3%) and negative predictive value (65.7%) of all OCT assessed features. - Conclusion: OCT-related morphological signs have a relatively high predictive value for the diagnosis of acute VKH.
Gesehen am 29.05.2019